Co-production between Ministry and Citizens - New challenges for program management - Jean-Marie Buijs; Jurian Edelenbos (European Regional Science Association (ERSA), 2005)
In this paper we discuss a co-production experiment in direct interaction between a department and citizens. In 2002 The Netherlands Ministry of Housing, Spatial Development and Environment (VROM) has started the program Citizen and Environment in order to make her environment policy to a greater extent of, for and by citizens. After an evaluation VROM decided to broaden the program to her entire policy field and the program changed into Policy with Citizens. This renewed Policy with Citizens program contains two goals: (1) citizen participation and (2) organizational change and learning. The two goals are strongly related, but also contain certain tensions. Citizens' participation as a goal can be developed at project level, but the aim of a more open organization is less concrete and probable more difficult to accomplish. This last goal requires a more process-oriented approach instead of a project approach. The program management has to maintain a connection between the short-term project results and long-term processes of organizational change. In this paper we will evaluate the management of first round of the Policy with Citizens program. It contains an exploration of barriers for co-production. We assume policy makers at national level will have to overcome barriers at personal, program and organizational level in order to increase the extern orientation of their organisation. We discuss competences they need in order to act successfully in co-production processes.
Keywords: 330